POLYCODE TEXTS IN RUSSIAN AS A FOREIGN LANGUAGE CLASSES (BASED ON THE SONG "THE LITTLE SYMPHONY ORCHESTRA" BY B. OKUDZHAVA) (Journal of Foreign Language Studies, 2025)
This study examines the use of polycode texts in teaching Russian as a foreign language. It aims to identify the advantages of this approach through the song "The Little Symphony Orchestra“by B. Okudzhava. The characteristics of polycode texts are often shaped by the development of the information society.. This study analyzes the linguistic and cultural features of B. Okudzhava’s song lyrics, then proposes a system of exercises in reading comprehension, text perception, and musical reproduction.
Keywords: polycode text; methodology; linguistic and cultural studies; mediation; literature